Insättningsrutinernas effekt på tillväxt samt effekten av klinisk sjukdom på ätbeteendet hos kalvar i gruppbox med automatisk mjölkutfodring - Olofsson, Maria (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
The aim of the present study was to investigate the effect of strategy for grouping calves into group pens with automatic milk-feeding systems on the calves' health and growth rate. The usefulness of changes in feeding behavior recorded by the computerized milk-feeder during periods of illness to identify calves with clinical diease was also studied.